(untitled) (The Strategic Review for Southern Africa, 2020)
Much of what we know about Zimbabwe’s liberation war heroes and heroines is associated with the Zimbabwe African National Union- Patriotic Front (ZANU-PF)’s recognition of individuals who defended its hold on power. However, of late, an upsurge in factionalism in the party has resulted in increasing reference to heroism as a means to exert factional dominance. An understanding of how this has been done can be used to explain ZANU-PF factional dynamics. Current studies call for the study of factionalism to focus on intra-party group dynamics instead of the traditional organisation forms of factions. It is in this context that this study argues that survival or fall of factions within (ZANU-PF) is framed around issues of heroism that is around one’s perceived contribution or non-contribution to the liberation struggle. This article demonstrates this growing phenomenon in ZANU-PF veteran leaders whose status has been reshaped by new political moments as factionalism intensified. Inlight of rising factionalism, we argue that, war hero/heroine status in ZANU-PF is not permanent, but is highly shaped by obtaining factional political moments.